Chronic Inflammatory Arthropathy Preceding Acute Systemic Manifestations of Sarcoidosis: A Possible Overlap of Idiopathic Juvenile Arthritis and Sarcoidosis - Matheus Campello Vieira; Priscilla Gomes Tosta; Fernanda Morello Nicole; Lucas Enock V. Roberto; Júlia Guasti P. Vianna; Paulo de Coelho Castro; Rafael Burgomeister Lourenço; Erica Vieira Serrano; Valéria Valim; Weverton Machado Luchi (Case Reports in Rheumatology)
Sarcoidosis is a multisystem disease with unknown etiology, marked by T lymphocytes and macrophages agglomeration, which leads to the formation of noncaseating granulomas in the affected tissues. We describe a case of a 40-year-old black patient referred to our service for evaluation of nephrolithiasis and persistent elevation of plasma creatinine. He reported important weight loss, fever episodes, and abdominal and low back intermittent pain in the past 6 months. The investigation revealed elevated serum calcium level, hepatosplenomegaly, retroperitoneal lymphadenopathy, anemia, thrombocytopenia, and nephrolithiasis. The initial diagnostic hypothesis was lymphoproliferative disease, but the laparoscopic propaedeutic showed multiple white lesions on the liver surface, which biopsy identified as noncaseating granulomas with asteroid corpuscles, suggestive of sarcoidosis. He was treated with corticosteroids with significant improvement in symptoms and in calcium and creatinine levels. Besides, the patient presented a long-term large joints arthropathy, especially on the knees (with bilateral prosthesis), wrists, and ankles, of unknown etiology. We discuss the systemic manifestations of sarcoidosis related to the reported case, as well as the possible overlapping of idiopathic juvenile arthritis with sarcoidosis.